Frequency of Neonatal Hypothermia in Preterm Infants Wrapped with and without Plastic Bag after delivery - Faiza Pervaiz, Maria Iqbal, Nadia Ejaz, Mahjabeen Akram, Sahar Fatima, Rafia Shoukat (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Preterm birth accompanies many complications including hypothermia that worsens neonatal health and may result in fatality if left untreated. Globally, plastic wraps are being used as a low-cost and effective method to maintain temperature. Aim: To compare frequency of neonatal hypothermia in preterm infants wrapped with and without plastic bag after delivery. Study design: This was randomized control trial. Methodology: This study was conducted using at Pediatrics department of SIMS hospital, Lahore, during 6 months. Data was collected using non-probability, consecutive sampling from a sample of 92 (46 newborns in each group). Infants randomized to group-B (no bag group) received standard hospital care based on WHO thermoregulation of the newborn protocol. The data was entered and analyzed in SPSS 23. Results: In plastic wrap group there were 32(69.57%) male and 14(30.43%) female cases while in no wrap group there were 27(58.70%) male and 19(41.30%) female cases, p-value >0.05. The median temperature after one hour was higher in plastic wrap and no wrap group was 37.6±0.7 and 36.85±1.80c respectively, p-value < 0.05. There were 3(6.5%) cases in plastic wrap group and 15(32.6%) of the cases in no wrap group who developed hypothermia, the frequency of hypothermia was statistically less in wrap group when compared with no wrap group, p-value <0.05. Practical Implication: However, there is limited literature in Pakistan that compares temperature maintenance among neonates wrapped and unwrapped with plastic bags. This investigation will help find better answers to this problem. Conclusion: It is concluded that the preterm infants wrapped with plastic bag after delivery had less frequency of neonatal hypothermia after 1 hour. Plastic wraps are effective, low cost and low resource friendly method that should be opted for temperature maintenance of preterm babies. Keywords: Hypothermia, Preterm Birth, Hyperthermia, plastic wraps, Neonates and Temperature